Potential of Manuka Honey as a Natural Polyelectrolyte to Develop Biomimetic Nanostructured Meshes With Antimicrobial Properties - Mancuso, Elena; Tonda-Turo, Chiara; Ceresa, Chiara; Pensabene, Virginia; Connell, Simon D.; Fracchia, Letizia; Gentile, Piergiorgio (Frontiers in Bioengineering and Biotechnology, 2019)
The use of antibiotics has been the cornerstone to prevent bacterial infections; however, the emergency of antibiotic-resistant bacteria is still an open challenge. This work aimed to develop a delivery system for treating soft tissue infections for: (1) reducing the released antimicrobial amount, preventing drug-related systemic side effects; (2) rediscovering the beneficial effects of naturally derived agents; and (3) preserving the substrate functional properties. For the first time, Manuka honey (MH) was proposed as polyelectrolyte within the layer-by-layer assembly. Biomimetic electrospun poly(ε-caprolactone) meshes were treated via layer-by-layer assembly to obtain a multilayered nanocoating, consisting of MH as polyanion and poly-(allylamine-hydrochloride) as polycation. Physicochemical characterization demonstrated the successful nanocoating formation. Different cell lines (human immortalized and primary skin fibroblasts, and primary endothelial cells) confirmed positively the membranes cytocompatibility, while bacterial tests using Gram-negative and Gram-positive bacteria demonstrated that the antimicrobial MH activity was dependent on the concentration used and strains tested.